Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Matematika tentang Operasi Hitung Campuran Bilangan Bulat dengan Model Pembelajaran Jigsaw - Suhaemi Suhaemi (Syntax Corporation Indonesia, 2023)
This study aims to improve Learning Outcomes through the Jigsaw Learning Model. The benefits of the research that the author formulated in this study are that students are able to understand the material of Integer Mixed Calculation Operations through the Jigsaw Learning Model.Based on the Learning model used, it was concluded that the results of learning evaluation have improved. This can be seen from the comparison of learning evaluation results between precycle, cycle I, and cycle II. In the precycle there were only 6 people (20%) out of 30 students who obtained scores above KKM (65), in the first cycle there were 17 people (56.7%) out of 30 students who obtained scores above KKM, and in the second cycle there were 29 people (96.66%) from 30 students who obtained scores above KKM with a grade point average of 83.66. So from these results, it can be concluded that the Jigsaw Learning Model can improve student learning outcomes in Mathematics lessons on Integer Mixed Calculation Operations material in grade V SDN Sirnagalih 03 Kec.Tamansari, Bogor Regency.